The Role of Mental Focus in Enhancing The Strength of The Attacking Player - Ali Abdyasir, Hussein (Pubmedia Jurnal Pendidikan Olahraga, 2026)
This paper was an investigation on the effectiveness of external attentional focus and guided imagery in improving the leg press strength and soccer-specific measures of an attacker on a simulated attacking player where Modeling 20 samples consisted of elite youth forwards/wingers who were aged 18-25 years and exposed to counterbalanced high versus low-focus tests in standard conditions high focus with external cues (drive through target) now coupled with 120-second kinesthetic imagery or low focus with no visualization. Key outcome measures were leg press strength (kg), power output (W), accuracy in the shot (percentage), sprint speed (km/h) and dribble success (percentage). The data was simulated with Monte Carlo (Python/NumPy) calibrated based on attentional focus meta-analyses (ES=0.58) producing a normally distributed measure: strength High M=85kg vs. Low M=75kg; power 450W vs. 400W. Significant improvements were established by paired t-tests by metrics (strength t=3.342, p=0.0034, d=1.18; power t=3.012, p=0.0072; accuracy t=4.244, p=0.0004; dribble t=6.465, p<0.0001). Mean improvement was 14.92% ( SD=4.36) or 8-50kg strength or 40-50W power gains. They were consistent in case of subgroup analysis (samples 1-10, 11-20) (all p<0.05). Focus variance was isolated by negative high-low correlations (-0.155 to -0.221). Results indicate that mental concentration results in medium-high impacts on attacking skills, equivalent to 0.25-0.5 goals/game possibilities. External attention maximizes motor programming of explosive actions supporting the constrained action hypothesis proposed by Wulf. Simulation scope limitations Limitations Future research needs to be physiologically validated (e.g., EMG, HRV). Findings recommend the consideration of short-term imagery fusion in soccer training, strength development without the conditioning aspect.